Strategy of Management of Pavo Muticus linnaeus Population in Bekol and Bama Savana of Baluran National Park: Strategi Pengelolaan Populasi Pavo Muticus linnaeus di Savana Bekol dan Bama Taman Nasional Baluran - Oktarino, Ilham Wijayanto (Yayasan Siti Widhatul Faeha, 2025)
This study aims to determine the management strategies and populations of green peacocks in bekol savanna and Bama savanna. The method of collecting data for the population is done by the Line Transect method which uses a path length of 2 Km with an unspecified path width and for spatial distribution carried out by stabilizing the coordinate points in each encounter and measuring the encounter distance and angle of encounter. And then it is managed by Geographic Information System. Whereas the strategy for optimizing the management of green peacock populations is used by in-depth interview method and Focus Group Disscustion (FGD) then it are analyzed descriptively, quantitatively. The results of the study carried out that population estimation was found for 27 individuals in Bekol savanna and 38 individuals in Bama savanna and having different sex ratio production at Bekol savanna had a ratio of male and female, which are 1: 2 and in Bama savanna had a 1: 4 sex ratio, and had a percentage of age structures dominated by adolescents from the two observation pathways, while the strategy for efforts to optimize the management of green peacock populations is obtained by the management of adaptive green peacock habitat to conduct regional management by increasing workforce personnel and maximizing cooperation in education and research from various partner institutions.